KAJIAN: FRAUD (KECURANGAN) LAPORAN KEUANGAN - Putri, Anisa (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2012)
Fraudulent misstatement or omission is deliberate amount or disclosures in financial statement. Perpetrators of fraud from people within the company can be from outside the company. Triggers fraud was caused by greed, needs, pressures, opportunities and rational.Financial statements contain material misstatements may result in financial statements are not presented fairly, in all material respects. Misstatement of financial statements may occur as a result of mistake or fraud. In order companies have a fraud prevention system, then the company makes detection systems, monitoring, reviewing policies and systems in the fields of human resources and operations.